Food Relocation Behavior, Nests, and Brood Balls of Canthon quinquemaculatus Laporte de Castelnau (Coleoptera: Scarabaeidae: Scarabaeinae) - Cantil, Liliana Fernanda (2014)
Individuals of Canthon quinquemaculatus Laporte de Castelnau rolled balls up to 4 m from the food source. Stealing balls was common. Male headstand position was observed at the entrance of chambers containing a rolled ball and a female. Nests were shallow, telecoprid, and compound. Male and female cooperate, and parental care is performed (Nesting Pattern V). A total of 23 brood balls from five nesting chambers were obtained from terraria. The brood balls display a protuberance that is separated from the provision chamber by a partition of soil material. An egg chamber that lacks an organic lining is located at the base of the protuberance. At the roof of the egg chamber, there is an aeration conduit that ends in a filter composed of loose soil. The carrion provisions contain a high percentage of soil material. Some brood balls have larval fecal pellets in the external surface of the wall. Egg chamber separated from provisions, lack of an organic lining coating the egg chambers, ejection of larval fecal pellets, and loose soil filters are typical characters of brood balls made by necrophagous Scarabaeinae. The first three characters might reflect a set of adaptive characters of the necrophagous species to their food. These characters might be useful to distinguish fossil brood balls constructed by necrophagous Scarabaeinae from those constructed by coprophagous species.